TANGGUNG JAWAB NEGARA DALAM PENYELESAIAN PELANGGARAN HAK ASASI MANUSIA - Sela Septika, Luh Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2017)
The existence of human rights infractions automatically raises the state's responsibility to resolve based on laws and regulations. The problem in this research is how the settings related to the completion of state responsibility for human rights infractions in the laws and regulations in Indonesia? and how efforts to resolve the human rights infractions committed by the state? The type of approach used is the conceptual approach and the statuteapproach. Article 28 paragraph (4) states that the protection, promotion, enforcement and fulfillment of human rights is the responsibility of the state. Article 28 paragraph (4) states that the protection, promotion, enforcement and fulfillment of human rights is the responsibility of the state, so that the molded Act No. 26 Year 2000 on Human Rights Court. Efforts to resolve the human rights violations can be observed through the provisions of Article 11 through Article 27 of the Law No. 26 Year 2000 on Human Rights Court.   Adanya pelanggaran hak asasi manusia secara otomatis memunculkan tanggung jawab negara untuk melakukan upaya penyelesaian sesuai peraturan perundangan-undangan.Permasalahan dalam penelitian ini adalah bagaimanakah pengaturan tanggung jawab negara terkait penyelesaian pelanggaran hak asasi manusia dalam peraturan perundang-undangan di Indonesia?serta bagaimanakah upaya penyelesaian pelanggaran hak asasi manusia yang dilakukan oleh negara? Jenis pendekatan yang digunakan adalah pendekatan konseptual dan pendekatan perudang-undangan.Pasal 28I ayat (4) menyebutkan perlindungan, pemajuan, penegakan, dan pemenuhan hak asasi manusia merupakan tanggung jawab negara, sehingga dibentuk Undang-Undang No. 26 Tahun 2000 tentang Pengadilan Hak Asasi Manusia yang mengatur upaya penyelesaian pelanggaran hak asasi manusia melalui ketentuan Pasal 11 sampai dengan Pasal 27.
Keywords: Human Rights; Infraction; Responsibility; Hak Asasi Manusia; Pelanggaran; Tanggung Jawab